Gliomatosis Cerebri: A Case Report - Cabrera Méndez, María Paula; Pontificia Universidad Javeriana (Pontificia Universidad Javeriana, 2013)
Gliomatosis cerebrii is a rare cerebral neoplasy, characterized by a diffuse infiltration of cerebral tissue without the formation of a tumoral mass. It is often manifested by inespecific neurological symptoms, which will vary according to the location of the lesion. It’s diagnosis is difficult, both clinically and radiologically, and it can be difficult to differentiate it from several other diseases. There is currently no optimum treatment strategy, and the prognosis of patients with this disease is very unfavorable. We present the case of a 17 year old male patient that developed this disease, followed by a review of the literature.